Hybrid PV/battery‐storage unit for residential applications. Issue 17 (4th April 2019) - Bagheri‐Farahbakhsh, Mina; Cross, Andrew; Strickland, Dani; Morris, Paul; Martin, Trevor; Lakin, Tony
Abstract : Under their 'Gone Green' deployment scenario, National Grid forecast that energy generated from photovoltaics (PV) in the UK is expected to rise from 2 to 15 GW over the next 20 years. This is being driven by the UK's legal obligations around installing renewable energy sources and cutting greenhouse gases, the rising cost of energy and concerns around the security of supply. Power electronic converters are a key enabling technology for PV and other low‐carbon technologies (LCTs). However, the use of LCTs can result in problems for the electrical distribution network such as supply voltage distortion and over‐voltages, which threaten to limit or delay their uptake. The project described here is investigating the use of GaN‐based converters in a hybrid PV/battery‐storage unit for residential applications. The potential for MHz operation of GaN offers smaller, lighter, more efficient, and lower cost converters compared with existing silicon‐based units and their deployment could lead to an increase in the installed LCT capacity on the network.